The greatest life lesson / Nor Asni Syahriza Abu Hassan - Abu Hassan, Nor Asni Syahriza (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.